Effect of palmitoylated prolactin-releasing peptide on food intake and neural activation after different routes of peripheral administration in rats - Mikulášková, Barbora; Zemenová, Jana; Pirník, Zdenko; Pražienková, Veronika; Bednárová, Lucie; Železná, Blanka; Maletínská, Lenka; Kuneš, Jaroslav (Peptides, 2016)
Obesity is an escalating epidemic, but an effective non-invasive therapy is still scarce. For obesity treatment, anorexigenic neuropeptides are promising tools, but their delivery from the periphery to the brain is complicated by their peptide character. In order to overcome this unfavorable fact, we have applied the lipidization of neuropeptide prolactin-releasing peptide (PrRP), whose strong anorexigenic effect was demonstrated. A palmitoylated analog of human PrRP (h palm-PrRP31) was injected in free-fed Wistar rats by three routes: subcutaneous (s.c.), intraperitoneal (i.p) (both 5 mg/kg) and intravenous (i.v.) (from 0.01 to 0.5 mg/kg). We found a circulating compound in the blood after all three applications with the highest concentration after i.v. administration. This corresponds to the effect on food intake, which was also strongest after i.v. injection. Moreover, this is in agreement with the fact that the expression of c-Fos in specific brain regions involved in food intake regulation was also highest after intravenous application. Pharmacokinetic data are further supported by results obtained from dynamic light scattering and CD spectroscopy. Human palm-PrRP31 analog showed a strong tendency to micellize, and formation of aggregates suggested lower availability after i.p. or s.c. application. We have demonstrated that palm-PrRP influenced food intake even in free fed rats. Not surprisingly, the maximal effect was achieved after the intravenous application even though two orders of magnitude lower dose was used compared to both two other applications. We believe that palm-PrRP could have a potential as an antiobesity drug when its s.c. application would be improved.
Keywords: obezita; CHO buňky; Receptors, G-Protein-Coupled; křečci praví; mozek; Drug Evaluation, Preclinical; energetický příjem; Humans; preklinické hodnocení léčiv; protoonkogenní proteiny c-fos; c-Fos; Protein Binding; hormon uvolňující prolaktin; Anti-Obesity Agents; krysa rodu Rattus; lidé; zvířata; neurony; CHO Cells; Food intake; Prolactin-Releasing Hormone; Cricetulus; Peptide Fragments; CD spectroscopy; Brain; Lipidization; vazba proteinů; Neurons; peptidové fragmenty; Cricetinae; Rats; Obesity; Animals; Pharmacokinetics; Proto-Oncogene Proteins c-fos; látky proti obezitě; receptory spřažené s G-proteiny; Energy Intake; Prolactin-releasing peptide